Comprehensive profiling of BRCA1 and BRCA2 variants in breast and ovarian cancer in Chinese patients. Issue 3 (24th December 2019) - Gao, Xianqi; Nan, Xiyan; Liu, Yilan; Liu, Rui; Zang, Wanchun; Shan, Guangyu; Gai, Fei; Zhang, Jingfeng; Li, Lei; Cheng, Gang; Song, Lele
Abstract: The identification and interpretation of germline BRCA1/2 variants become increasingly important in breast and ovarian cancer (OC) treatment. However, there is no comprehensive analysis of the germline BRCA1/2 variants in a Chinese population. Here we performed a systematic review and meta‐analysis on such variants from 94 publications. A total of 2, 128 BRCA1/2 variant records were extracted, including 601 from BRCA1 and 632 from BRCA2 . In addition, 414, 734, 449, and 307 variants were also recorded in the BIC, ClinVar, ENIGMA, and UMD databases, respectively, and 579 variants were newly reported. Subsequent analysis showed that the overall germline BRCA1/2 pathogenic variant frequency was 5.7% and 21.8% in Chinese breast and OC, respectively. Populations with high‐risk factors exhibited a higher pathogenic variant percentage. Furthermore, the variant profile in Chinese is distinct from that in other ethnic groups with no distinct founder pathogenic variants. We also tested our in‐house American College of Medical Genetics‐guided pathogenicity interpretation procedure for Chinese BRCA1/2 variants. Our results achieved a consistency of 91.2–97.6% (5‐grade classification) or 98.4–100% (2‐grade classification) with public databases. In conclusion, this study represents the first comprehensive meta‐analysis of Chinese BRCA1/2 variants and validates our in‐house pathogenicity interpretation procedure, thereby providing guidance for further PARP inhibitor development and companion diagnostics in the Chinese population.